The Nexus between Residential Density, Travel Behavior and Traffic Congestion in Developing Metropolitans: A Case Study of Harare, Zimbabwe - James Kanyepe (Journal of Contemporary Urban Affairs, 2023)
There is a noticeable dearth of empirical studies on the mediating role of travel behaviour on the influence of residential density on traffic congestion in developing countries, particularly in Zimbabwe. To address this gap, this study examined the effect of residential density on traffic congestion and delved into the potential mediating role of travel behaviour in this relationship. This study used data from a sample of 384 households in the Harare metropolitan province of Zimbabwe. Structural equation modelling was used to test the research hypotheses. The findings indicate that residential density and travel behaviour have a positive effect on traffic congestion. The results also established that travel behaviour partially mediates the relationship between residential density and traffic congestion. This study adds to the existing body of knowledge by providing an array of indicators that can inform policymakers in transportation and urban planning to alleviate traffic congestion.